Analisis Faktor-Faktor yang Mempengaruhi Kemandirian Keuangan Daerah Provinsi Jawa Tengah - Regita Cahyaningrum; P. Eko Prasetyo (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Financial independence is one of the goals of decentralization in Central Java over a period of 28 years. Fiscal independence shows an upward trend, while inequality, open unemployment rates, human development indices, and economic growth also show similar upward trends. The objective of this study is to analyze the impact of inequality, open unemployment rates, the Human Development Index, and economic growth—both in the long term and short term—on regional financial independence in Central Java. This study is a quantitative study using secondary data in the form of time series data from 1996 to 2023 sourced from the Central Statistics Agency (BPS), processed using the Eviews 12 application with the Vector Error Correction Model (VECM) analysis method. The results indicate that, in the long term, the open unemployment rate and economic growth have a significant negative impact on regional financial autonomy. The Human Development Index has a significant positive impact, while inequality does not have a significant impact on regional financial autonomy. In the short term, both at lag 1 and lag 2, only economic growth has a significant negative impact on regional financial autonomy. Thus, inequality is more of a consequence than a determinant of regional fiscal conditions, unemployment affects regional financial independence in the long term, the Human Development Index influences regional financial independence in the short term, and economic growth does not guarantee an increase in regional financial independence. Local governments need to maintain equitable development, reduce structural unemployment, improve workforce skills, and integrate human resource quality with local economic strengthening. Additionally, they should optimize the PAD sector and taxation to ensure that economic growth directly impacts local fiscal capacity.